GEOMETRISCHE THEORIE DER \(p\)-ANALYTISCHEN FUNKTIONEN - Čanak, Miloš; Protić, Ljubomir (Matematichki Bilten, 1995)
In this paper the theory of vector fields and particularly, a notion of vector of deviation of analyticity in obtaining one classification of \(p\)-analytic functions.